Validación del Q-PAD: cuestionario para la evaluación de psicopatología en adolescentes. (2023)
The main objective of this study was to contribute to the validation of the Questionnaire for the Evaluation of Psychopathology in Adolescents (Q-PAD) in a nonclinical sample of Colombian adolescents. The sample consisted of 559 students of a center of public secondary education. Correlations between 9 Q-PAD subscales were significant and positive, except for the self-esteem subscale. The internal structure of each scale showed an essentially unidimensional structure, except for the Psychosocial Risk subscale. The internal consistency for the subscales ranged between 0.78 and 0.91 (McDonald's omega). The exploratory factor analysis yielded a solution of 6 factors. A good external validity between the Q-PAD Family Problems subscale and the three subscales of Interpersonal Relations Scale (ERI) was observed. The results indicate that scores of Q-PAD have an appropriate psychometric support and this instrument would allow screening for psychosocial and mental health problems in Colombian adolescents in an efficient, easy, fast and non-invasive way.